Edukasi Pendidikan Anti Korupsi Bagi Pelajar dan Remaja di SMA Negeri 1 Medan - Maltus Hutagalung; Micael Jeriko Damanik; Marihot Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to educate students and adolescents at SMA Negeri 1 Medan about the importance of anti-corruption education. This activity is motivated by the increasing attention to preventing corruption from an early age, by instilling the values of integrity, honesty, and responsibility in the educational environment. The implementation method includes interactive counseling, group discussions, and case simulations relevant to students' daily lives. Participants consisted of 180 students from grades 11 and 12 who actively participated in each session. The results of the activity showed an increase in students' understanding of the basic concepts of corruption, types of corruption, and the important role of the younger generation in creating an anti-corruption culture. This education is expected to be the first step in shaping students' character with integrity and legal insight from an early age.